Searching Life, the Universe and Everything? The Implementation of Summon at the University of Huddersfield - Stone, Graham (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
A review of the recent literature suggests that users prefer simple search interfaces such as Google. The implication here is that libraries often fail to make their resources discoverable and that this may in turn affect the perceived value of the library. Against the background of the ongoing national debate about user expectations, a project group at the University of Huddersfield was asked to investigate the current provision for electronic resources and to look at a solution which would ‘provide ease of searching and access for the user, whilst reducing the workload for systems and technical services and remaining within current budget levels’. As a direct result of this review, the University of Huddersfield was the first UK commercial adopter of Summon in the summer of 2009. The Summon web-scale discovery service from Serials Solutions provides a simple single-search box to the breadth of the library’s collection, swiftly delivering simultaneous information and results from the local catalogue and remote electronic resources offering a real alternative to the traditional federated search. This paper will provide a case study of the implementation, evaluation and launch of this radical new service to users at the University of Huddersfield, by detailing the approaches used and lessons learned throughout the implementation period and making recommendations for future enhancements.